Improving menstrual health literacy in sport - McGawley, K.; Sargent, D.; Noordhof, D.; Badenhorst, C. E.; Julian, R.; Govus, A. D. (Journal of Science and Medicine in Sport, 2023)
Menstrual health represents a state of complete physical, mental, and social well-being in relation to a woman's menstrual cycle. From a health literacy perspective, knowledge acquisition and expertise are dependent upon the degree to which an individual can find, access, understand, critically analyse, and apply health information. Therefore, menstrual health literacy can be used to describe the state of knowledge acquisition and application specific to menstrual health-related issues. Menstrual health literacy is low among female athletes, their coaches, and practitioners, and few evidence-informed education or implementation strategies exist to improve menstrual health literacy in sport. Moreover, athletes seldom discuss their menstrual cycles or hormonal contraceptive use with their coaches, despite experiencing menstrual symptoms and/or disturbances and perceiving their menstrual cycles/hormonal contraceptive use to affect performance. Barriers to communication about menstrual cycle- and hormonal contraceptive-related topics include a perceived lack of knowledge among athletes, coaches, and practitioners, concerns about how conversations on these issues will affect interpersonal relationships, and a lack of formal and informal discussion forums. Whilst evidence relating to the effects of the menstrual cycle phase and hormonal contraceptive use on training and performance is currently limited, with existing studies often lacking methodological rigour, impactful steps can still be made to support female athletes. This cornerstone review highlights the current state of menstrual health literacy among athletes, coaches, and practitioners, and provides recommendations for improving menstrual health literacy in sport.